Diagnostic Performance of Dengue Virus Envelope Domain III in Acute Dengue Infection - Nguyen, Ngoc Minh (Int J Mol Sci, 2019)
Dengue, one of the most prevalent illnesses caused by dengue viruses that are members of the genus Flavivirus, is a significant global health problem. However, similar clinical symptoms and high antigenic homologies with other Flaviviruses in the endemic area pose difficulties for differential diagnosis of dengue from other arbovirus infections. Here, we investigated four types of recombinant envelope protein domain III (DV-rED III) derived from four dengue virus (DENV) serotypes for diagnostic potential in detecting IgM in acute phase (mainly 2–3 days after onset of fever). Each independent DV-1, -3, and -4-rED III-ELISA showed less than 60% sensitivity, but the combined results of DV-1, -3, and -4-rED III-ELISA led to sensitivity of 81.82% (18/22) (95% CI, 59.72 to 94.81) and 100% specificity (46/46) (95% CI, 92.29 to 100.00) as each antigen compensated the other antigen-derived negative result. In conclusion, the independent combination of data derived from each recombinant antigen (DV1-, DV3-, and DV4-rED III) showed comparable efficacy for the detection of IgM in patients with acute-phase dengue infection.